(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article discusses proper nouns in Uzbek texts and methods for their determination. It studies the expression of common nouns in NLP and their linguistic features. Detailed definitions of the concepts of NE and NER, their properties, methods of definition and their use in texts are given.